Estimation of genetic parameters as well as trends for growth traits in Harnali sheep - SEHGAL, TARUN; DAHIYA, SATPAL; DALAL, D S; PATIL, C S; RATWAN, POONAM; BANGAR, YOGESH (The Indian Journal of Animal Sciences, 2024)
The current study focussed on the growth traits pertaining to Harnali sheep maintained at Sheep Farm, LUVAS, Hisar and data were recorded from pedigree sheets of 1278 animals. Growth traits considered were birth weight (BW), weaning weight (WW), six-month weight (6MW), yearling weight (YW), and pre-weaning average daily gain (PRWDG) and least-squares means for corresponding traits found to be 3.28±0.02 kg, 12.89±0.07 kg, 17.06±0.06 kg, 24.36±0.06 kg, and 106.74±0.61 g, respectively. Effect of different factors like period of birth, sex of animal and dams’ weight at lambing was studied on growth traits. Except YW, significant effect of period of birth was observed on all the growth traits. Sex had significant influence on BW only however, dams’ weight at lambing affected significantly all the considered growth traits except YW. By leveraging the sire component of variance and covariance from mixed model analysis, the paternal half-sib correlation method was used to estimate genetic as well as phenotypic parameters. Estimates of heritability for BW, WW, 6MW, YW and PRWDG were 0.28±0.07, 0.33±0.07, 0.31±0.07, 0.12±0.04 and 0.27±0.06, respectively. Genetic as well as phenotypic trends for WW and PRWDG were found to be positive. Moderate range of genetic variability at weaning weight and its positive genetic and phenotypic correlations with growth traits specially six month’s weight indicated that genetic improvement could be possible through early selection at weaning weight in Harnali sheep.